Diseño del sistema de rodillos gofradores para el moldeado de cera de abeja. - Chiluisa Palomo, Erika Alexandra (2020)
Designing a system of engraving rollers to mold the beeswax was the objective of this research, in order for beekeepers to access the product that is important to them, The research uses quantitative methodology in the dimensional design, comparing between different design alternatives and the most appropriate solution, and experimental to determine the plate size and the alveolus, since through these data and results will be obtained in the system. In addition, when designing the engraving rollers, software applied to engineering will be used, which will be SolidWork in the student version, this will help in the design and modeling of them, taking into account that an improvement will be made in the part of the alveoli and automate the system, also ANSYS FLUENT for a CAE analysis. Using CAD software, a deformation analysis will be performed, efforts, which are presented in the embossing rollers and their components, in addition to a load study on the design structure. The beeswax behavior is simulated, with CAE software use for its respective validation, taking into account that it must be used in the engineering part before any manufactured process.